THE INFLUENCE OF CAPITAL, LIQUIDITY, CREDITS, AND COST EFFICIENCY ON PROFITABILITY OF BANKING INDUSTRY IN INDONESIA - Helma Malini (Cakrawala Management Business Journal, 2021)
This study aims to examine and analyze the effect of capital adequacy, liquidity, non-performing credit, and cost efficiency on profitability (a study on the group of national foreign exchange commercial banks in Indonesia for the period 2012-2018). This research was conducted with a quantitative approach. The population in this study is the National Private Commercial Bank company in Indonesia in the 2012-2018 period. The total sample was 49 banking companies which were selected by using the purposive sampling method, the analytical type used descriptive analysis and multiple regression analysis. The results of the study, among others, show that the CAR variable has a positive direction and has a significant effect on profitability, the LDR variable has a negative and insignificant direction on profitability, while the NPL variable has a negative but not significant effect on profitability. BOPO variable has a negative and significant effect on profitability. Simultaneously, these variables can influence profitability at the National Private Commercial Bank in Indonesia.